First-Time Mothers Have a Desire to Be Offered Professional Breastfeeding Support by Pediatric Nurses: An Evaluation of the Mother-Perceived-Professional Support Scale. (6th August 2019) - Ranch, Matilda Möller; Jämtén, Sofia; Thorstensson, Stina; Ekström-Bergström, Anette C.
Abstract : Background . Although the World Health Organization recommends exclusive breastfeeding for six months, the rate of breastfeeding has decreased worldwide. Breastfeeding is the natural way of feeding a baby, but it is a process that has to be learnt. It is not unusual for problems to occur and hence support for breastfeeding is vital. The aim of this study was to explore first-time mothers' experiences of the breastfeeding support offered by pediatric nurses, as well as to develop and evaluate the Mother Perceived Support from Professionals (MoPPS) scale. Methods . A qualitative design involving both inductive and deductive approaches was chosen. Nine first-time mothers were interviewed regarding their experiences of the breastfeeding support offered by pediatric nurses. Semistructured interviews were conducted. The mothers were also asked to grade their experiences of breastfeeding support on the MoPPS scale. A qualitative content analysis was applied when analyzing the data obtained using both the inductive (interviews) and deductive (MoPPS scale) approaches. Results . The results revealed that the mothers felt the desire to breastfeed, although they all experienced some difficulties. They wanted the pediatric nurses to be perceptive and provide professional support based on their own experiences. When the pediatric nurses took time and booked extra appointments, the mothers felt supported. The inductive analysis resulted in one theme: "When wanting to breastfeed, mothers have a desire to be offered professional breastfeeding support". Two main categories were identified, namely "Mothers wanted but lacked breastfeeding support" and "Mothers received professional support." The deductive analysis of the MoPPS scale showed similar results, and the questions were perceived as relevant to the aim. The mothers considered it important that the pediatric nurses had sufficient knowledge about breastfeeding. It was also considered important that the pediatric nurses involved the mothers' partners in the breastfeeding support. Therefore, we suggest that these areas should be included in the MoPPS scale for pediatric nurses. Conclusions . The MoPPS scale can be a useful tool for helping pediatric nurses to offer mothers professional breastfeeding support. Indeed, when offering breastfeeding support, pediatric nurses can use the items included on the MoPPS scale as guidance.